ANALISIS KINERJA SIMPANG BERSINYAL DI SIMPANG PAPAR UNTUK PERENCANAAN JALAN TOL KERTOSONO-KEDIRI - Endro Wibisono; Muhammad Shofwan Donny Cahyono; Adhi Muhtadi (U Karst, 2019)
The Papar intersection is a very congested route because the location is in the Kertosono-Kediri toll road planning area for the economic distribution of the Western and Southern East Java Provinces. There needs to be a traffic engineering management so that the intersection is not increasingly saturated. As a benchmark is the forecasting of traffic performance carried out for 2 years from 2019 to 2021. The intersection of the Simpang Papar due to the construction of the Kertosono-Kediri toll road will decrease the value of the DS by developing the Kertosono-Kediri toll road so that the DS value is below 1 (one). The lowest 2021 DS is 0.17, while the highest DS is 0.46. Based on the results of forecasting, the intersection of Papar after the construction of the Kertosono - Kediri toll road has increased the volume of traffic along with the growth in vehicle numbers. The lowest 2045 DS year is 0.94, while the highest DS is 2.51. The solution to dealing with traffic congestion in the year 2045 is by traffic monitoring, especially the signal settings and vehicle restrictions.Â Keywords : Traffic Performance, Degree of Saturation, Signal Intersection, Toll PlanningPersimpangan Papar adalah rute yang sangat padat karena lokasinya berada di area perencanaan jalan tol Kertosono-Kediri untuk distribusi ekonomi Provinsi Jawa Barat dan Jawa Timur Selatan. Perlu ada manajemen rekayasa lalu lintas agar persimpangan tidak semakin jenuh. Sebagai patokan adalah peramalan kinerja lalu lintas yang dilakukan selama 2 tahun dari 2019 hingga 2021. Persimpangan Simpang Papar karena pembangunan jalan tol Kertosono-Kediri akan menurunkan nilai DS dengan mengembangkan tol Kertosono-Kediri jalan sehingga nilai DS di bawah 1 (satu). 2021 DS terendah adalah 0,17, sedangkan DS tertinggi 0,46. Berdasarkan hasil peramalan, persimpangan Papar setelah pembangunan jalan tol Kertosono - Kediri telah meningkatkan volume lalu lintas seiring dengan pertumbuhan jumlah kendaraan. Tahun 2045 DS terendah adalah 0,94, sedangkan DS tertinggi adalah 2,51. Solusi untuk menangani kemacetan lalu lintas pada tahun 2045 adalah dengan memonitor lalu lintas, terutama pengaturan sinyal dan pembatasan kendaraan.Kata Kunci: Performa Lalu Lintas, Derajat Kejenuhan, Persimpangan Sinyal, Perencanaan Tol